ZOONYMS AS NATIONAL SPECIFIC MEANS CREATING IMAGES IN THE ENGLISH AND UZBEK LANGUAGES - Khodjaeva, Muslimakhon Ravshanjon kizi; Shukurova, Shokhsanam Kakhramon kizi (Educational Research in Universal Sciences, 2023)
The article illustrates the importance of a national world picture in terms of zoonyms and classifies them reflecting the image of the English and the representative of Uzbeks. Moreover, the authors give examples in both languages for each group of the classification.